Transesterification via direct-ultrasonic irradiation of rubber seed oil with waste materials based heterogeneous catalyst - Amin, M.M. (Italian Association of Chemical Engineering - AIDIC, 2015)
Present process of transesterification faces various challenges. The most challenging is to obtain high conversion rate when using high free fatty acid (FFA) feedstock. The aim of this study is to investigate transesterification process of rubber seed oil (RSO) through direct-ultrasonic irradiation (UI) with addition of waste material based heterogeneous catalyst. The waste material based heterogeneous catalyst derived from empty fruit bunch (EFB) was prepared using incipient wetness impregnation method. System parameters such as reaction time, reactants molar ratio, ultrasonic amplitude and catalyst amount were studied. Properties of free fatty acid (FFA) content were measured for RSO and RSO-ester product. Characterization of catalyst was done using X-ray diffraction analyses and it was found that potassium was the primary component of the ash. Esterification with acid sulphuric (H2SO4) catalyst using direct-ultrasonic irradiation successfully reduced the FFA value in rubber seed oil to less than 2 with application of 30 amplitude frequency in 20 min. However transesterification with waste material heterogeneous catalyst (KOH/EFB) under direct-ultrasonic irradiation showed low conversions of fatty acid methyl ester (FAME). Copyright Â© 2015, AIDIC Servizi S.r.l.,.